Autistic Spectrum Difficulties - Mortimer, Hannah (Leamington Spa : Scholastic, 2002)
Many groups will at some point include children who have autistic spectrum difficulties. This title should help all early years professionals to recognize and understand such difficulties and to provide inclusive activities.
Keywords: Autistic children -- Education; Special education; Education